Laporan Kasus : Krisis Hiperglikemi pada Pasien Diabetes Wanita Usia 45 tahun dengan Edema Paru - Sherliana, Ria (Journal of Islamic Medicine, 2022)
Hyperglycemic crisis is a metabolic emergency that causes morbidity or death. Diabetic Ketoacidosis (DKA), and Hyperosmolar Hyperglycemic State (HHS), are 2 forms of hyperglycemic crisis that often occur in patients with uncontrolled diabetes mellitus. A 45-year-old female patient came to the hospital emergency department with decreased consciousness since 12 hours and shortness of breath since 2 days. The patient has a history of diabetes mellitus. On physical examination, E2V2M4 consciousness, blood pressure 140/90, oxygen saturation 40% with a reservoir bag oxygen mask 15 liters per minute, coarse rhonchi and chest retractions. From the results of investigations, there was an increase in blood glucose (523 mg/dL), a chest X-ray of pulmonary edema and bilateral bronchopneumonia. The patient was diagnosed with a hyperglycemic crisis with unstable hemodynamics. However, before being transferred to the intensive care unit, the patient was declared dead. Hyperglycemic crisis is a metabolic emergency whose management must be fast and appropriate in order to maintain hemodynamic stability and prevent death Keyword :Diabetes, Diabetic ketoacidosis, Hyperglycemic crisis, Hyperosmolar hyperglycemic state